Kajian Historisme dalam Cerpen “Yasima Ingin Jadi Juru Masak Nippon” karya Edy Firmansyah: Analysis of Historicism in Short Story “Yasima Ingin Jadi Juru Masak Nippon” by Edy Firmansyah - Putri, Lara Anastasya; Hartanto, Erika Citra Sari (Kibas Cenderawasih, 2023)
Not too many people use Historicism as a theory in their research. The use of the Historicism approach aims to identify historical events. The source of the data used in this research is a short story entitled Yasima Ingin Jadi Juru Masak Nippon by a writer named Edy Firmansyah. The research method used in this research is a qualitative method. The results and discussion found that the short story of Yasima Ingin Jadi Juru Masak Nippon by a writer named Edy Firmansyah has historical values, most of the parts focus on the wars that occurred in the past when the Madurese people fought against the Dutch and Japanese colonizers. Thus, the researcher hopes that this research can be used as research material by future researchers.